Dimeric Cyclobutane Formation Under Continuous Flow Conditions Using Organophotoredox‐Catalysed [2+2] Cycloaddition. Issue 4 (7th December 2021) - Grantham, Helena F.; Kimber, Marc C.
Abstract: Radical‐cation‐initiated dimerization of electron rich alkenes is an expedient method for the synthesis of cyclobutanes. By merging organophotoredox catalysis and continuous flow technology, a batch versus continuous flow study has been performed providing a convenient synthetic route to an important carbazole cyclobutane material dimer 1, 2‐ trans ‐dicarbazylcyclobutane (t‐DCzCB) using only 0.1 mol % of an organophotoredox catalyst. The scope of this methodology was explored giving a new class of functional materials, as well as an improved synthetic route to styrene‐based lignan dimeric natural products. The cyclobutane dimers could be isolated in higher chemical yields under continuous flow conditions and reaction times were reduced significantly compared to traditional batch reaction conditions. Abstract : A good combination : Dimeric cyclobutane building blocks have been synthesized by merging organophotoredox catalysis and continuous flow technology. This method was validated using several types of electron rich alkene substrates with measurable advantages over traditional batch reaction conditions.